New insights into lipid metabolism of Haematococcus pluvialis in response to high-light stress - Scodelaro Bilbao, Paola Gabriela (2018)
The oleaginous unicellular microalga Haematococcus pluvialis is being intensely studied as a source of carotenoids and lipids with potential biotechnological and biomedical applications. The aim of this study was to analyze the effect of high-light stress on the regulation of triacylglyceride (TAG) and sterol synthesis in H. pluvialis UTEX 2505. After 24 hours of high-light exposure, both lipid classes significantly increased compared to the control condition. As expected, the use of inhibitors of the Kennedy pathway cerulenin, propranolol, xanthohumol and A922500 significantly decreased TAG synthesis under high-light stress, while mevastatin and 25-hydroxycholesterol reduced sterol content. These results were coincident with qPCR and Western blot analyses and also revealed some of the enzymes of H. pluvialis involved in lipid synthesis in response to high-light. In addition, we observed that Kennedy pathway inhibitors yet reduced sterol content while sterol biosynthesis inhibitors also diminished TAG production, denoting a coordination between both synthesis pathways. Fosmidomycin, a specific inhibitor of the non-mevalonate pathway of isoprenoid biosynthesis, reduced total carotenoid content and antioxidant capacity together with TAG and sterol content. Finally, inhibition of carotenoid, TAG and sterol synthesis significantly reduced cell viability suggesting their participation in H. pluvialis survival and adaption to high irradiance. These findings reveal features of lipid synthesis and function of H. pluvialis under high-light stress, and points towards new possible molecular targets to enhance lipid production in microalgae.